Inspection of Maqasid al-Syari’ah in Religious Texts Regarding the Recommendation to Shave Underarm Hair - Ali Akhbar Abaib Mas Rabbani Lubis; Abdul Rafik (Cakrawala: Jurnal Studi Islam, 2020)
This study discusses the aesthetics of personal grooming which includes recommendations for shaving armpit hair. This study aims to better understand the aesthetics of personal grooming and hadiths regarding the recommendation to remove armpit hair in terms of al-mashlahah’s approach, al-Syatibi’s perspective. The method of this study was qualitative which involves a literature review. The explanation is analyzed through three stages which include the stages of data condensation, data display, and conclusion-verification. The results found that the aesthetics of personal grooming in Islam accordance with maqasid al-shari’ah because of its hygiene and health perspective. For that, shaving the armpit hair is in accordance with the objectives of shari’, which is to bring benefits (mashlahat) and prevent disease (mafsadat).